METHODOLOGY FOR ORGANIZING LANDSCAPE COMPOSITIONS IN STUDENTS OF GENERAL AND SPECIALIZED ART SCHOOLS - Tursunova Dilshoda Jahongirovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Annotation: This article examines the methodology for organizing landscape compositions in students of general and specialized art schools. It explores pedagogical approaches, didactic techniques, and practical exercises aimed at developing students’ compositional skills, visual perception, and creative thinking. The study highlights effective strategies for guiding learners in structuring landscape elements, achieving harmony in composition, and enhancing their artistic competence. Additionally, the article considers the differences in methodology for general versus specialized art school settings, emphasizing tailored approaches to meet students’ varying skill levels and educational needs.